2021
DOI: 10.1002/cpz1.268
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Sequential Response Learning in the Rodent Operant Touchscreen System

Abstract: Sequential and cue-directed response learning in rodents have been previously shown to depend on intact striatal signaling. In particular, these behaviors rely on striatal dopamine and acetylcholine release, with an impairment of sequential response learning evident in animal models with alterations in the two systems. Here we provide a protocol for testing sequential response/response chain learning using the rodent touchscreen system. Specifically, the present protocol is designed to implement the heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…To better understand operant responding in mutant mice, we modified the protocol of the heterogeneous sequence task as described by Keeler et al (2014) 30 and adapted it for touchscreens (see Janickova, Kljakic et al 2021). 47 Similar to the FR and PR tasks, mice had to respond a white square stimulus multiple times in order to get a reward.…”
Section: Heterogenous Sequence Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand operant responding in mutant mice, we modified the protocol of the heterogeneous sequence task as described by Keeler et al (2014) 30 and adapted it for touchscreens (see Janickova, Kljakic et al 2021). 47 Similar to the FR and PR tasks, mice had to respond a white square stimulus multiple times in order to get a reward.…”
Section: Heterogenous Sequence Taskmentioning
confidence: 99%
“…To better understand operant responding in mutant mice, we modified the protocol of the heterogeneous sequence task as described by Keeler et al (2014) 30 and adapted it for touchscreens (see Janickova, Kljakic et al 2021). 47 Similar to the FR and PR tasks, mice had to respond a white square stimulus multiple times in order to get a reward. However, in the heterogeneous sequence task, the stimulus was presented sequentially in five different locations on the screen from the left to the right, so mice were required to make five sequential responses, each to one of the five windows.…”
Section: Heterogenous Sequence Taskmentioning
confidence: 99%
“…There are currently several alternatives that allow a detailed testing of motor or operant learning and flexibility. Among those, the touchscreen-based systems offer a great number of pre-designed paradigms that can be modified and allows creating additional, custom made tasks (Horner et al, 2013;Mar et al, 2013;Heath et al, 2016;Janickova et al, 2021). However, a significant cost of such systems may be prohibitive for some users and it also makes it less attractive for occasional users that are not specializing in this kind of behavioral testing.…”
Section: Discussionmentioning
confidence: 99%
“…In these paradigms, it may be difficult to capture subtle changes in animal's behavior as a simple motor action does not allow for a detailed insight (Keeler et al, 2014). In literature, several elegant paradigms can be found that are suitable for testing more complex motor learning and automatization (Keeler et al, 2014;Geddes et al, 2018;Dhawale et al, 2021;Janickova et al, 2021;Turner et al, 2022;Wolff et al, 2022). However, these tasks usually do not involve flexibility part (although they could be probably adapted to it) and, more importantly, they often require a specialized equipment and/or technical expertise which makes them less accessible.…”
Section: Introductionmentioning
confidence: 99%
“…In these paradigms, it may be difficult to capture subtle changes in the behavior of an animal as a simple motor action does not allow for a detailed insight ( Keeler et al, 2014 ). In the literature, several paradigms can be found that are suitable for testing more complex motor learning and automatization ( Keeler et al, 2014 ; Geddes et al, 2018 ; Dhawale et al, 2021 ; Janickova et al, 2021 ; Turner et al, 2022 ; Wolff et al, 2022 ). However, these tasks usually do not involve flexibility, and, more importantly, they often require specialized equipment and/or technical expertise, which makes them less accessible.…”
Section: Introductionmentioning
confidence: 99%